RANKL Cytokine: From Pioneer of the Osteoimmunology Era to Cure for a Rare Disease - Nadia Lo Iacono; Alessandra Pangrazio; Mario Abinun; Robbert Bredius; Marco Zecca; Harry C. Blair; Paolo Vezzoni; Anna Villa; Cristina Sobacchi (Clinical and Developmental Immunology)
Since its identification, the RANKL cytokine has been demonstrated to play a crucial role in bone homeostasis and lymphoid tissue organization. Genetic defects impairing its function lead to a peculiar form of autosomal recessive osteopetrosis (ARO), a rare genetic bone disease presenting early in life and characterized by increased bone density due to failure in bone resorption by the osteoclasts. Hematopoietic stem cell transplantation (HSCT) is the only option for the majority of patients affected by this life-threatening disease. However, the RANKL-dependent ARO does not gain any benefit from this approach, because the genetic defect is not intrinsic to the hematopoietic osteoclast lineage but rather to the mesenchymal one. Of note, we recently provided proof of concept of the efficacy of a pharmacological RANKL-based therapy to cure this form of the disease. Here we provide an overview of the diverse roles of RANKL in the bone and immune systems and review the clinical features of RANKL-deficient ARO patients and the results of our preclinical studies. We emphasize that these patients present a continuous worsening of the disease in the absence of a cure and strongly wish that the therapy we propose will be further developed.